Implementing Cognitive Reading Strategies in ELT Class Room Situation - Murniati Saddu (Universitas Lancang Kuning, 2015)
This present study investigated the reading strategies which ELT students generally used when they read a text,and which strategies they needed to develop to understand a text better and to continue their academic studies successfully.The study aimed to find the answers to the following questions; (1) Which cognitive reading strategies are used by theuniversity students in their academic studies?, (2) What sort of cognitive reading strategies should be developed by thesestudents in order to continue their academic studies successfully and to get the most out of a text they read?. The populationof this study was composed of the 1st and 4th year students in English Department at Klabat University. Menado.Two different methods were used to collect data. In the first part, a self-report questionnaire consisting of 25 items wasadministered to 185 students. In the second part, Think-Aloud Protocol was conducted with 23 subjects. Reading strategieswere evaluated under three headings: pre-reading, while-reading, and post-reading in both parts. The results of TAPsanalysis revealed that the students used only one strategy namely, “relating the title to the text content” in the pre-readingphase. As for the while-reading phase, the most effectively employed strategies were: using the dictionary parsimoniously,guessing the meaning of a word from the context, skipping some unknown words, thinking-aloud during reading, andassimilating the text with the background knowledge. However, none of the post-reading strategies were found to be usedby the participants. The data collected from the questionnaire was analyzed statistically. The results of the analysis indicatedthat there were some significant differences on the effective use of cognitive reading strategies with regard to students’gender, age, and proficiency in reading, school source, and duration in learning English.